Milk quality and subclinical mastitis in dairy herds in the province of Huaura, Lima Peru - Velásquez V., Carlomagno (2012)
This research was conducted in the province of Huaura, Lima-Peru in 2009-2010 to determine the quality of milk through Somatic Cell Count (SCC) in milk tanks of three dairy herds and four small farmer associations in two seasons of the year, and to assess subclinical mastitis by the California Mastitis Test (CMT) in 32 farms (2100 cows), considering parity, herd size and lactation phase. No statistical difference was found between large dairy herds (755.4 ± 46.9 x 103 cells/ml) and farmer associations (752.1 ± 41.1 x 103 cells/ml); however, there were differences between farms (p <0.05). The RCS in summer (957.1 ± 54.1 x 103 cells/ml) was higher than in winter (550.3 ± 35.5 x 103 cells/ml) (p <0.05). A greater proportion of CMT positive quarters were observed in medium and large herds compared to small herds (52.6 and 49.9% vs 29.8% respectively) (p <0.05), in cows with >2 parities in comparison to 1st and 2nd calvers (40.8 vs 32.8 and 24.8% respectively) (p <0.05), and in cows in late lactation compared to mid and early lactation (40.3 vs 38.2, and 23.2% respectively) (p<0.05). Milk from Huaura dairy farms associations does not meet the Peruvian quality standards in terms of RCS. Subclinical mastitis was associated with herd size, parity, and time of lactation.